Is the society in india envious of its doctors? A doctor's perspective - B Sadananda Naik (Wolters Kluwer Medknow Publications, 2020)
It is very disheartening that society in India which has a long history and tradition of revering its medical professionals is slowly and steadily becoming indifferent to them. This is a write up on this issue from a doctor's perspective.